Prosperity in the Twenty-First Century Concepts, models and metrics - Moore, Henrietta L.; Davies, Matthew; Mintchev, Nikolay; Woodcraft, Saffron (Global Prosperity in Thought and Practice, 2023)
Prosperity in the Twenty-First Century sets out a new vision for prosperity in the twenty-first century and how it can be achieved for all. The volume challenges orthodox understandings of economic models, but goes beyond contemporary debates to show how social innovation drives economic value. Drawing on substantive research in the UK, Lebanon and Kenya, it develops new concepts, frameworks, models and metrics for prosperity across a wide range of contexts, emphasising commonalities and differences. Its distinctive approach goes beyond defining and measuring prosperity - addressing the debate about the failures of GDP - to formulating and describing what is needed to make prosperity a realisable proposition for specific people living in specific locales. Departing from general propositions about post-growth to delineate pathways to prosperity, the volume emphasises that visions of the good life are diverse and require empirical work co-designed with local communities and stakeholders to drive change. It is essential reading for policymakers who are stuck, local government officers who need new tools, activists who wonder what is next, academics in need of refreshment, and students and people of all ages who want a way forward.